Eco-compatible oxides enabling energy storage via Li+/Mg2+ co-intercalation. Issue 36 (29th August 2019) - Veleva, Sv.; Ivanova, Sv.; Półrolniczak, P.; Wasiński, K.; Nihtianova, D.; Stoyanova, A. E.; Stoyanova, R.
Abstract : The co-intercalation of Li + and Mg 2+ into magnesium manganates and lithium titanates allow using them as electrodes in hybrid Li–Mg ion cells with conventional lithium electrolyte. Abstract : The storage of energy by means of reversible intercalation of bivalent magnesium ions represents, nowadays, the shortest route for doubling the energy density of conventional lithium ion batteries. Contrary to the intercalation of monovalent lithium ions, the intercalation of Mg 2+ is a kinetically limited process. Herein we demonstrate a new approach for improving Mg 2+ intercalation, which is based on dual intercalation of Li + and Mg 2+ ions with a synergic effect. The concept is proved on the basis of eco-compatible oxides such as magnesium manganate spinels, MgMn2 O4, and lithium titanates Li2 TiO3 and Li4 Ti5 O12 with a monoclinic and spinel structure. These two types of oxides are selected since they exhibit high and low potentials of ion intercalation due to the redox couples Mn 2, 3+ /Mn 3, 4+ and Ti 3+ /Ti 4+, respectively. Through a newly developed method of synthesis, we succeeded in the preparation of well-crystallized nanosized spinels with a specific cationic distribution. The intercalation properties of MgMn2 O4, Li2 TiO3 and Li4 Ti5 O12 are first examined in model cells versus the metallic Li anode. The Li + and Mg 2+ intercalation is directed by the kind of the used electrolyte: a lithium electrolyte consisting of 1 M LiPF6 solution in EC : DMC and a magnesium electrolyte consisting of 0.5 Mg(TFSI)2 solution in diglyme. The mechanism of Li + and Mg 2+ co-intercalation is assessed by ex situ X-ray diffraction and high-resolution transmission electron microscopy (HR-TEM). Finally, a new type of hybrid Li–Mg ion cell combining MgMn2 O4 and Li4 Ti5 O12 oxides as electrodes is constructed. The cell configuration allows reaching an operating voltage of around 1.7 V by using an electrolyte containing 0.5 M LiTFSI in diglyme.